The Alleged Decline of Liberation Theology: Natural Death or Attempted Assassination? - Cousineau, Madeleine (Religions, 2022)
Is liberation theology dead or in decline? This article analyzes factors that have led to that perception and provides evidence to the contrary. It demonstrates that the theology has survived multiple attempts by certain sectors of both church and state to eliminate it, and that it remains very much alive in grassroots pastoral programs and social movements. Support for this last statement is provided by the author’s field research in Brazil. The article concludes with signs that liberation theology will endure as it continues to inspire spiritually motivated people who commit themselves to addressing human needs by promoting social justice.